The suppression of DC‐link voltage fluctuations through a source active current feedforward in the active power filter. Issue 3 (28th January 2021) - Meng, Runquan; Du, Yi; Han, Xiaoqing; Wang, Peng
Abstract: An active power filter (APF), which operates under the power‐balance‐based scheme (PB scheme), suffers heavier DC‐link voltage fluctuation when the loads change suddenly, so that it is apt to be interfered and degraded or even out of stable operation. By analyzing the cause of DC‐link voltage fluctuation, this study proposes an improved PB scheme which feeds forward the increment of the fundamental‐frequency positive sequence component of the source current. The feed‐forward channel is designed by use of the cascaded delayed signal cancellation algorithm and integrated into the conventional PB scheme APF without adding any extra hardware circuit. The current increment fed forward is added into the output of the voltage controller to timely amend the reference current of the current control loop, and thus the active power flow, which caused by loads change, between the APF and its external circuitry can be suppressed. As a result, the DC‐link voltage fluctuation is mitigated to allow the APF to better accommodate the abrupt load changes. The configuration of the improved control system is introduced and the stability is analysed. The experiment results demonstrate the effectiveness of the proposed control scheme.